Single-cell technology reveals the crosstalk between tumor cells and immune cells: driving immune signal transduction and inflammation-mediated cardiac dysfunction in the tumor microenvironment of colorectal cancer - Nie, Wenyang; Zhang, Wangzheqi; Xiahou, Zhikai; Meng, Yuxuan; Liu, Yuhang; Zhang, Jingwen; Wang, Zhen; Wang, Yong (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) is a heterogeneous illness influenced by intricate tumor-immune interactions and characterized by a dismal prognosis. Macrophage-mediated immunological signaling facilitates tumor proliferation and may associate inflammation in the tumor microenvironment (TME) of CRC with negative outcomes. Notwithstanding therapeutic advancements, resistance to treatment remains a significant obstacle. scRNA-seq offers comprehensive insights into the immune signaling network and immunological dynamics inside the CRC’s TME.MethodsWe integrated scRNA-seq data from GEO with extensive RNA-seq data from TCGA to elucidate immunological signaling and dynamic cellular variation in the TME of CRC. The analyses encompassed quality control via Seurat, InferCNV, Monocle, CellChat, and SCENIC, differential gene expression, inference of copy number variation (CNV), pseudo time trajectories, and intercellular communication. Prognostic modeling was conducted using Cox regression and LASSO. Immune infiltration and drug sensitivity were evaluated by CIBERSORT, ESTIMATE, xCell, TIDE, and pRRophetic. Functional validation encompassed siRNA knockdown, qRT-PCR, Western blot analysis, and cellular assessment in CRC cell lines.ResultsWe discovered four categories of tumor cells exhibiting variations in cell cycle, stemness, and differentiation. The MKI67+ subpopulation exhibited a heightened dynamic cell state and engaged with macrophages via the MIF-(CD74+CD44) axis to facilitate immunological signaling. HMGA1 is a crucial transcription factor in this fraction, and its knockdown impedes CRC cell proliferation, motility, and invasion. The cancer model utilizing the MKI67+ TCs subpopulation (MTRS) successfully classified patient survival and linked with immune infiltration patterns and medication responses. Enrichment analysis revealed tumor-promoting and immunological signaling networks. Correlation scores suggest that this subpopulation may be linked to inflammation and immunosuppression inside the TME.ConclusionOur research indicates that the C2 MKI67+ TCs subpopulation is a key driver of immune signal transduction in CRC TME, which may induce inflammatory responses through interaction with macrophages, thereby leading to adverse consequences such as cardiac dysfunction. HMGA1 represents a viable target for immunotherapy, and our cancer model derived from this subpopulation offers prognostic significance and direction for immunotherapeutic treatments.